2021
DOI: 10.1002/nml.21486
|View full text |Cite
|
Sign up to set email alerts
|

Racialized minorities, trust, and crisis: Muslim‐American nonprofits, their leadership and government relations during COVID‐19

Abstract: The COVID‐19 pandemic disproportionately affects already‐vulnerable minorities, highlighting the need for strong, trusting relationships between governments and minority nonprofits for everyone's benefit. The current scholarship suggests minority members often lack trust in government. This study contributes to the field by examining trust levels Muslim‐American nonprofits have for federal, state, and local government. Nearly two‐thirds (65%) of Muslim nonprofit leaders believe that they may be discriminated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Can a broader understanding of philanthropy from a Muslim perspective open up new and innovative ways to include more people within the social good? A recent report found that Muslim Americans give at much higher rates than the general American population, to religious and non-religious causes (Noor et al, 2021). However, this report uses the frames of monetary giving and voluntary hours.…”
Section: Discussionmentioning
confidence: 97%
“…Can a broader understanding of philanthropy from a Muslim perspective open up new and innovative ways to include more people within the social good? A recent report found that Muslim Americans give at much higher rates than the general American population, to religious and non-religious causes (Noor et al, 2021). However, this report uses the frames of monetary giving and voluntary hours.…”
Section: Discussionmentioning
confidence: 97%
“…The events of 9/11 may have affected Muslim nonprofits in other ways. Increased Islamophobia may have affected their reputation and increased instability and anxiety in the sector (Noor et al, 2022; Wasif, 2021). Consequently, research shows how Muslim nonprofits worked harder than other peer organizations to demonstrate their credibility post-9/11 (Thaut et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…All of the challenges experienced during COVID‐19, like other large‐scale crises, demand robust governance and leadership particularly when they are happening in turbulent social environments characterized by globalization, new technology, political divides, and mediatized communication (Ansell et al, 2021 ; Ansell & Trondal, 2018 ; Noor et al, 2021 ). More specifically, nonprofits are required to have adaptive and flexible leadership structures to strategically adjust operations and programs, adopt new technology and tap into various capacities, reexamine their crisis leadership teams and communication strategies, and revisit their budgets to improve the likelihood of their survival.…”
Section: Literature Reviewmentioning
confidence: 99%